Actualization of Pancasila Values (Indonesian Ideology) in Majelis Taklim Organization - Rika Erliyana; Samsul Huda (Al-Hayat: Journal of Islamic Education, 2019)
This research begins based on observations of many cases of decadence in the actualisation of Pancasila values in various fields, especially in the field of education. Because of the lack of students' understanding of the importance of actualising Pancasila values in all aspects of life. This type of research is research and development (R & D). The results of this study: the more their awareness of the importance of divinity values, deepened their understanding of the significance of tasammuh attitude (morality), members of Majelis Taklim (Islamic study organization) prioritize public interests over personal and group interests, the existence of fair and free deliberation in determining activity plans, and their increased awareness of the importance of implementing simple life behaviors. The results of quantitative data analysis show that the products developed are feasible to be used as learning media in the activities of the Taklim Assembly Organization. This evidenced by the study of the overall data of the validator, and the score of 3.93 is in the "Good" category. The constructor response score to the module in a small scale trial was 82% in the "very high" grade. Observation of the improvement in the ability of the coaches by applying the modules in small-scale experiments reached 86.33%, and large-scale trials reached 90%, which were both in the "very high" category. Penelitian ini diawali berdasarkan pengamatan banyak kasus-kasus dekadensi aktualisasi nilai-nilai Pancasila dalam berbagai bidang, terutama dalam bidang pendidikan. Karena kurangnya pemahaman siswa akan pentingnya mengaktualisasikan nilai-nilai Pancasila dalam segala aspek kehidupan. Jenis penelitian ini adalah penelitian dan pengembangan (R&D). Hasil penelitian: semakin bertambahnya kesadaran mereka terhadap pentingnya nilai ketuhanan, memperdalam pemahaman mereka mengenai pentingnya sikap tasammuh (berakhlak), siswa anggota Majelis Taklim (organisasi pengkajian Islam) lebih mengutamakan kepentingan umum di atas kepentingan pribadi dan golongan, adanya musyawarah yang adil dan bebas berpendapat dalam menentukan rencana kegiatan, serta bertambahnya kesadaran mereka akan pentingnya menerapkan perilaku hidup sederhana. Hasil analisa data kuantitatif menunjukan bahwa produk yang dikembangkan layak untuk digunakan sebagai media pembelajaran dalam kegiatan Organisasi Majelis Taklim. Hal ini dibuktikan berdasarkan analisa data keseluruhan validator diperoleh skor 3,93 yang berada pada kategori â€œBaikâ€. Skor respon pembina terhadap modul dalam uji coba skala kecil sebesar 82% yang berada pada kategori â€œsangat tinggiâ€. Observasi peningkatan kemampuan pada pembina dengan menerapkan modul pada uji coba skala kecil mencapai 86,33% dan uji coba skala besar mencapai 90% yang sama-sama berada pada kategori â€œsangat tinggiâ€.